Cobalt(II)-Catalyzed Oxidative Coupling of Aromatic Tertiary Amines with Enol Silyl Ethers Leading to β-Aminoketone Derivatives - Sakai, Norio; Muraoka, Takuya; Matsumoto, Shun; Mutsuro, Akihiro; Ogiwara, Yohei (Synlett, 2017)
We demonstrated that a cobalt(II)-TBHP (tert-butyl hydroperoxide) oxidizing system efficiently catalyzes the coupling of aromatic tertiary amines with enol silyl ethers, producing the corresponding β-aminoketones.
Keywords: cobalt; oxidation; aromatic tertiary amine; enol silyl ether; β-aminoketone